p53 mediated regulation of LINE1 retrotransposition derived R-loops - Paul, Pratyashaa; Kumar, Arun; De, Astik Kumar; Parida, Ankita Subhadarsani; Bhadke, Gauri; Khatua, Satyajeet; Pattanayak, Fizalin; Tiwari, Bhavana (bioRxiv, 2024)
Long Interspersed Nuclear Element 1 (LINE1/L1) retrotransposons, comprising around 17% of the human genome, typically remain quiescent in healthy somatic cells but become activated in various cancer types. Our recent investigation reveals that p53 silences L1 transposons in human somatic cells, potentially constituting a tumor suppressive pathway. In this study, we demonstrate that p53 silences both L1mRNA-gDNA (cis L1 R-loops) and L1mRNA-cDNA hybrids (trans L1 R-loops) formed during retrotransposition. The activation of L1 transposons by HDAC inhibitors (HDACi) led to accumulation of these cis and trans L1 R-loops in p53-/- cells, which were mitigated by treatment with a reverse transcriptase inhibitor. Furthermore, p53 established re-silencing of hyperactivated L1 transposons induced by HDACi. The p53-mediated restoration of silencing was accompanied by recruiting histone repressive marks specifically H3K9me3 and H3K27me3 and inhibiting the deposition of H3K4me3 and H3K9ac marks at the L1 promoter. This study elucidates a novel role of p53 in regulating the formation of RNA-DNA hybrids, a pivotal intermediate component of retrotransposition, and initiating the suppression of hyperactivated L1 elements. These findings underscore the significance of p53 in preserving genome stability through the regulation of L1-derived R-loops. The role of L1 transposon derived L1mRNA-cDNA hybrids; an intermediate product formed during retrotransposition, in DNA damage and inflammation is not clear. Paul et al. reveals that p53 prevents L1cDNA derived RNA-DNA hybrids to control DNA damage and activation of inflammatory genes. The findings also elucidate the role of p53 in initiating the repression of hyperactivated transposons by facilitating the recruitment of epigenetic repressive marks and preventing the deposition of activating marks at L1-5’UTR. p53 loss facilitates accumulation of both cis (L1mRNA-gDNA) and trans (L1mRNA-cDNA) forms of L1 R-loops. The youngest, actively retrotransposing full-length L1s contribute to the formation of trans (L1mRNA-cDNA) R-loops. p53 aids immediate L1 re-silencing by restoring deposition of epigenetic repressive and inhibition of activating marks. Reverse transcriptase inhibitor prevents L1 mediated DNA damage. Subject Categories: L1/LINE1, p53, Retrotransposons, RNA-DNA hybrids, Cis R loops, Trans R-loop, L1/LINE1